ONCOFERTILITY AS AN OPPORTUNITY FOR CANCER PATIENTS TO HAVE CHILDREN – A LITERATURE REVIEW - Wiktoria Garbacz,; Edyta Szymańska,; Adrianna Maria Mikołajczyk,; Patryk Pustuła,; Anna Maria Pietrzak,; Zuzanna Natalia Burkacka,; Kacper Konrad Kmieć,; Zofia Szypuła,; Hanna Eve Feder, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Oncofertility is a field that combines specialisations in oncology and reproductive medicine. Fertility preservation methods should be presented to the patient before the start of cancer treatment. Proposals should be tailored to the patient's age, gender, type of cancer and future treatment.Aim: This review aims to present a comprehensive overview of the impact of cancer treatment on the gonads and methods of fertility preservation after cancer treatment.Material and Methods: An in-depth literature review was performed using PubMed, Google Scholar and ScienceDirect, including keywords such as: ‘oncofertility’, ‘oncology’, ‘cancer’, ‘gynaecological cancers’, ‘methods of fertility preservation’, “chemotherapy” and ‘cancer treatment’.Results: Fertility preservation methods vary depending on gender and age. In women, we can use oocyte, embryo and ovarian tissue fragment freezing, hormonal suppression and oophorectomy. Research is ongoing to increase the range of methods offered, including uterine transposition, in vitro maturation, in vitro gametogenesis, uterine transplantation, and artificial ovaries. For male patients, options include ejaculate freezing, testicular tissue freezing, or hypothalamic-pituitary axis suppression. For patients before puberty, the only option for preserving fertility is to freeze fragments of the gonads.Conclusion: The number of cancer diagnoses is increasing. Patients should be informed about all possible options for preserving fertility. Further research is needed to increase the options for having children for patients after cancer treatment.